Securing Cloud PCs and Azure Virtual Desktop Start implementing and optimizing security for Windows 365 and AVD infrastructure - Verham, Dominiek; Verham, Dominiek; Vanneuville, Johan; Brinkhoff, Christiaan (Packt Publishing, 2024)
Enhance your security expertise in Microsoft virtual desktops by exploring the latest security controls and use cases to safeguard your Windows 365 and Azure Virtual Desktop infrastructureKey FeaturesUnderstand the importance of securing your endpoints and overcome security challengesLearn about the latest Microsoft security controls for Windows 365 and AVDGain an understanding of securing virtual environments through various use casesPurchase of the print or Kindle book includes a free PDF eBookBook DescriptionDo you want to effectively implement and maintain secure virtualized systems? This book will give you a comprehensive understanding of Microsoft virtual endpoints, from the fundamentals of Windows 365 and Azure Virtual Desktop to advanced security measures, enabling you to secure, manage, and optimize virtualized environments in line with contemporary cybersecurity challenges. You$1 (Bll start with an introduction to Microsoft technologies, gaining a foundational understanding of their capabilities. Next, you$1 (Bll delve into the importance of endpoint security, addressing the challenges faced by companies in safeguarding their digital perimeters. This book serves as a practical guide to securing virtual endpoints, covering topics such as network access, data leakage prevention, update management, threat detection, and access control configuration. As you progress, the book offers insights into the nuanced security measures required for Windows 365, Azure Virtual Desktop, and the broader Microsoft Azure infrastructure. The book concludes with real-world use cases, providing practical scenarios for deploying Windows 365 and Azure Virtual Desktop. By the end of this book, you$1 (Bll be equipped with practical skills for implementing and evaluating robust endpoint security strategies.What you will learnBecome familiar with Windows 365 and Microsoft Azure Virtual Desktop as a solutionUncover the security implications when company data is stored on an endpointUnderstand the security implications of multiple users on an endpointGet up to speed with network security and identity controlsFind out how to prevent data leakage on the endpointUnderstand various patching strategies and implementationsDiscover when and how to use Windows 365 through use casesExplore when and how to use Azure Virtual Desktop through use casesWho this book is forThis book caters to a diverse audience within the IT landscape. For IT directors and decision makers, it provides valuable insights into the security benefits of implementing virtual desktops, emphasizing the contribution to a more secure environment. IT consultants and engineers will find practical tools and guidance for securely managing Microsoft cloud-based virtual desktops. Security professionals will benefit from the expert knowledge and alignment with industry best practices, while students can deepen their understanding of securing AVD and W365.s